2016
DOI: 10.1007/s00395-016-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide treatments as adjuncts to reperfusion in acute myocardial infarction: a systematic review of experimental and clinical studies

Abstract: Unmodified reperfusion therapy for acute myocardial infarction (AMI) is associated with irreversible myocardial injury beyond that sustained during ischemia. Studies in experimental models of ischemia/reperfusion and in humans undergoing reperfusion therapy for AMI have examined potential beneficial effects of nitric oxide (NO) supplemented at the time of reperfusion. Using a rigorous systematic search approach, we have identified and critically evaluated all the relevant experimental and clinical literature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 62 publications
(78 reference statements)
0
54
0
Order By: Relevance
“…Interestingly, GTN treatment per se did not interfere with cardiac protection afforded by remote ischemic preconditioning in patients undergoing coronary surgery [30]. A critical evaluation of all the relevant experimental and clinical literature to assess whether exogenous NO (NO gas, nitrite, nitrate or NO donors) given at reperfusion can limit infarct size, revealed highly protective effects for most experimental studies whereas the benefit of these interventions in clinical myocardial infarction is unproven [3].…”
Section: Etohmentioning
confidence: 98%
“…Interestingly, GTN treatment per se did not interfere with cardiac protection afforded by remote ischemic preconditioning in patients undergoing coronary surgery [30]. A critical evaluation of all the relevant experimental and clinical literature to assess whether exogenous NO (NO gas, nitrite, nitrate or NO donors) given at reperfusion can limit infarct size, revealed highly protective effects for most experimental studies whereas the benefit of these interventions in clinical myocardial infarction is unproven [3].…”
Section: Etohmentioning
confidence: 98%
“…It is well established that hypercholesterolaemia is accompanied by a decrease in cardiac NO content and increased nitro‐oxidative stress; however, the role of NO donors in ischaemia/reperfusion injury with or without hypercholesterolaemia is not well established. Although NO treatment prior to or during the early reperfusion period can limit infarct size in preclinical studies, the excessive production of NO at the beginning of reperfusion reacts with ROS and forms peroxynitrite (see for reviews: Andreadou et al ., ; Bice et al ., ). The three clinical studies with NO donors that have been performed so far have revealed no evidence of infarct size reduction in patients treated with NO donors immediately prior to reperfusion.…”
Section: Effect Of Hypercholesterolaemia On Myocardial Ischaemia/repementioning
confidence: 99%
“…Additionally, high concentrations of NO can promote cellular injury, a situation that is possible in patients being treated with several co‐medications including nitrates. Hence, cardioprotection by NO donors should be demonstrated in experimental models with co‐morbidities and relevant co‐medications prior to clinical translation (Ferdinandy et al , ; Andreadou et al , ; Bell et al ., ; Bice et al ., ).…”
Section: Effect Of Hypercholesterolaemia On Myocardial Ischaemia/repementioning
confidence: 99%
“…In a study by Lang et al [120], using NO inhalants after liver transplantation protected hepatocytes, promoted liver function recovery, and shortened the duration of hospital stay. In a meta-analysis by Bice et al [121], NO interventions also limited infarct size during the early reperfusion period. In myocardial injury, inhaled gaseous NO inhibited cardiomyocyte apoptosis and reduced infarct size [122-125].…”
Section: Nitric Oxide Corresponding Protection Strategymentioning
confidence: 99%